Selected Topics on Socio-technical Perspective in Information Systems: Editorial Introduction to Issue 22 of CSIMQ - Peter Bednar; Alexander Nolte (Complex Systems Informatics and Modeling Quarterly)
This thematic issue of the Complex Systems Informatics and Modeling Quarterly (CSIMQ) journal is dedicated to fostering a socio-technical perspective in the Information Systems (IS) field. The contemporary perspective has developed a lot over the years and the socio-technical agenda continues to be relevant.  The issue contains a selection of extended papers presented at STPIS’19 – 5th International Workshop on Socio-Technical Perspective in IS Development held on June 10, 2019 in Stockholm, Sweden in conjunction with the 27th European Conference on Information Systems (ECIS). The workshop featured presentations of 13 papers and 3 posters and was attended by more than 30 participants from 8 different countries (Sweden, Norway, Finland, UK, Germany, Italy, Switzerland, and the US). Four of the presented papers were extended for publication in this special issue. The articles presented in this thematic issue contain at least 30% new material compared to the papers initially submitted for the workshop. The last included article was submitted as a regular contribution to the CSIMQ journal and was selected to be included into this thematic issue because of its close connection to the topic of socio-technical systems.